2008
DOI: 10.1093/bioinformatics/btn365
|View full text |Cite
|
Sign up to set email alerts
|

Apparently low reproducibility of true differential expression discoveries in microarray studies

Abstract: Based on a statistical model, we show that even in technical replicate tests using identical samples, it is highly likely that the selected DEG lists will be very inconsistent in the presence of small measurement variations. Therefore, the apparently low reproducibility of DEG detection from current technical replicate tests does not indicate low quality of microarray technology. We also demonstrate that heterogeneous biological variations existing in real cancer data will further reduce the overall reproducib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
124
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(127 citation statements)
references
References 49 publications
3
124
0
Order By: Relevance
“…However, for higher MV percentages the majority of genes will have at least one MV, so by evaluating a wide range of missing percentages we feel that addresses this issue indirectly. Another limitation is that the false discovery rate was not evaluated separately, and recent studies have shown that subsamples of expression matrices can produce gene lists with low FDRs (Zhang et al, 2008). One last point is our use of the term 'biological' impact.…”
Section: Discussionmentioning
confidence: 99%
“…However, for higher MV percentages the majority of genes will have at least one MV, so by evaluating a wide range of missing percentages we feel that addresses this issue indirectly. Another limitation is that the false discovery rate was not evaluated separately, and recent studies have shown that subsamples of expression matrices can produce gene lists with low FDRs (Zhang et al, 2008). One last point is our use of the term 'biological' impact.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, when there are many highly correlated features, different ones may be selected under different settings [8]. On the other hand, even there are no redundant features, the existence of multiple non-correlated sets of real markers is also possible [15].…”
Section: Causes Of Instabilitymentioning
confidence: 99%
“…The PO (percentage of overlaps) metric is frequently used to evaluate the consistency of different lists (26,36,37). Clearly, to be used as a disease marker for a disease, a differentially expressed miRNA should have a steady regulation pattern across different data sets.…”
Section: The Po Scorementioning
confidence: 99%
“…Importantly, this result also suggests that the differentially expressed miRNA in a particular cancer has a consistent up-or downregulation pattern. On the analysis of different samples for each cancer, the miRNA displaying the most pronounced differential expression varied greatly, which could be attributed to biological variation of the molecular change of miRNA in the samples (26). On the basis of the biological assumption that 2 differentially expressed miRNAs with significantly overlapped targets may have a similar function (27), we proposed a score entitled percentage of overlaps of function-related miRNAs (POF) to evaluate the functional consistency of differentially expressed miRNAs for a cancer.…”
Section: Introductionmentioning
confidence: 99%